(untitled) (IMC Journal of Medical Science, 2021)
Background and objectives: Metformin improves manifestations of polycystic ovary syndrome (PCOS) by reducing insulin resistance. The objective of this study was to determine how metformin, in combination with lifestyle changes, affects the clinical manifestations of PCOS. Materials and Methods: Patients with PCOS attending the outpatient of a tertiary care hospital were enrolled in the study. Revised Rotterdam Consensus 2003 criteria were used to diagnose cases of PCOS. Clinical information, anthropometric measurement, serum progesterone and polycystic ovarian morphology (PCOM) of each subject were recorded in a prescribed data sheet at baseline and after a period of nine months. Randomized placebo controlled double blind design was used to assign participants in respective groups. Participants were randomly assigned to receive 9-month course of either metformin (1500 mg/day) or placebo. Both groups were advised regarding schedule of lifestyle modification. Outcome variables were clinical manifestations related to metabolic, reproductive and androgenic status of PCOS. Results: Out of 80 enrolled PCOS cases, 49 completed the study (metformin=26, placebo=23). The mean age of the study participants of metformin and placebo groups was 23.52±5.18 and 22.09±3.58 years respectively (p=0.262). Menstrual cycle significantly improved in both the study groups (before vs. after - metformin: 19.2% vs. 76.9%, p=0.003; placebo: 19.2% vs. 47.8%, p=0.02) after 9 months, but compared to placebo group no such significant (p=0.12) improvement occurred in metformin group. Severity of hirsutism, presence of acne, serum progesterone level and ovulatory status improved significantly in both groups after completion of the study. Except acanthosis nigricans, other metabolic manifestations did not significantly improve in metformin compared to placebo group after the intervention. While comparing the percentage changes, body mass index (BMI) and waist circumference (WC) reduced significantly in metformin than placebo group (BMI in kg/m2- metformin vs. placebo: -3.63±8.22 vs. +1.42±6.67, p= 0.024; WC in cm - 2.81±7.74 vs. +1.68±7.89, p= 0.05). No significant adverse event was observed in metformin group. Conclusion: Metformin, in conjunction with lifestyle modifications, has favorable impacts on clinical manifestations of PCOS. Ibrahim Med. Coll. J. 2021; 15(2): 1-12